VNTR Variant of the eNOS Gene and its Relationship with Osteoporosis in Postmenopausal Turkish Women - Nursal, Ayse F.; Yigit, Serbulent; Tekcan, Akin; Ozsoy, Asker Z.; Ates, Haci O. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Background: Osteoporosis (OP) is the most common type of systemic bone disease characterized by low bone mass and micro-structure deterioration of bone tissue, with a consequent increase in bone fragility and fracture risk. Nitric oxide (NO), produced by the enzyme endothelial nitric oxide synthase (eNOS) in endothelial cells, has considerable effects on bone cell function. The objective of this case-control study was to investigate the potential association between the eNOS gene Variable Number Tandem Repeat (VNTR) variant and susceptibility of OP, in Turkish postmenopausal female patients. Methods: One hundred and fifty female patients and 100 age-matched healthy females were enrolled in the present study. The eNOS gene VNTR variant was genotyped with a polymerase chain reaction (PCR) method. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to assess the strength of the association. Results: The mean age of the patients was 60.32±8.65 years. It was found that the eNOS VNTR variant genotype and allele frequencies were not significantly different between the patient and control groups (p>0.05).
Keywords: endothelial nitric oxide synthase